Implications of inter observer variability in cervical smear reporting - Sushma, .; Jacob, Roshny (International Journal of Research in Medical Sciences, 2017)
Background: In spite of the Bethesda system 2001 (TBS 2001), formulating strict guidelines for reporting cervical smears, intra observer and inter observer variations are unavoidable and can be considered an inherent part of the reporting system. The implications of this variation are in the quality of performance of the reporting laboratory and in the patient management. Rescreening is a tool to reduce the variations and improve the quality of both the laboratory staff and laboratory as such. Rescreening by two or more experienced observers has helped in identifying new cases better. The present study aims to rescreen cervical smears by two independent observers, to compare the results of the two independent observers and to understand the implications of this variability on the quality of cervical smear reporting. Methods: 1000 consecutive cervical smears were rescreened by two experienced cyto-pathologists independently. Their findings were charted out and analyzed statistically for kappa value. Results: Initial reporting had identified 20 cases of neoplastic nature. First observer identified, in addition, 6 new cases and second observer identified 12 new cases. The inter observer variability of 6 cases showed a kappa value of 0.89. Conclusions: Rescreening is a safe way of picking up missed cases. Rescreening by two or more observers is better in identifying new cases. This helps in improving the quality of reporting personnel and the laboratory as well as in improving patient care.